Dielectric ceramic composition, and electronic component
Patent Information
- Application Number
- JP2023133319
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-03-03
AI Technical Summary
【0010】 本開示の誘電体磁器組成物は、高温域での安定性に優れ、良好な誘電体特性に加え、耐久性を有する。
Smart Images

Figure 2025028477000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a dielectric ceramic composition and an electronic component. [Background technology]
[0002] Dielectric electronic components (e.g., capacitors) have traditionally been used as key components in a variety of electronic devices, including home appliances. 3 Dielectric ceramic compositions containing BaTiO 3 Since the Curie point (Curie temperature) of is about 125° C., the relative dielectric constant drops significantly in a high temperature range exceeding 150° C. compared to room temperature. To address this problem, the capacitors disclosed in Patent Documents 1 and 2 are disclosed.
[0003] In Patent Document 1, (K 1-y Na y )Sr 2 Nb 5 O 15 The dielectric ceramic composition is represented by a tungsten bronze type composite oxide mainly composed of, and does not contain Pb, and has a Curie point higher than that of BaTiO3.
[0004] Patent Document 2 describes the composition formula (K a Na b Li c C d ) e DO f Disclosed is a capacitor using a dielectric ceramic composition including a first crystal phase made of a niobium / tantalate alkali perovskite oxide represented by the formula: (element C is at least one of alkaline earth metals Ca, Sr, and Ba; element D is at least one of Nb and Ta; a, b, c, and d satisfy a+b+c+d=1; 0.97≦e≦1.10, f is optional) and a second crystal phase made of an A-Ti-BO composite oxide (element A is an alkali metal; element B is at least one of Nb and Ta; the contents of element A, element B, and Ti are all non-zero). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2006 / 114914 [Patent Document 2] JP 2013-028484 A Summary of the Invention [Problem to be solved by the invention]
[0006] In recent years, with the electrification of vehicles, there has been a demand for directly mounting electrical circuit boards near the engine room or around the motor, which become hot, in order to save space. As the temperature of the operating environment for in-vehicle electrical components increases, dielectric capacitors are also required to have a high relative dielectric constant, excellent durability, and stability against temperature changes, even at higher temperatures (for example, 200°C-250°C).
[0007] However, in the dielectric ceramic composition described in Patent Document 1, BaTiO 3 Although it has a higher Curie point than BaTiO, it has a large dielectric loss (tan δ) and is not suitable for practical use. 3 It has a higher Curie point, a high dielectric constant, and good stability against temperature changes, but no indication has been given regarding durability.
[0008] The present disclosure has been made in consideration of the above-mentioned circumstances, and has an object to provide a dielectric ceramic composition having excellent stability in a high temperature range, good dielectric properties and durability. The present invention can be realized in the following aspects. [Means for solving the problem]
[0009] a first crystal phase made of an alkali niobate-based perovskite oxide; A dielectric ceramic composition comprising: The second crystal phase contains Li and Ti, A dielectric ceramic composition, wherein when the second crystal phase is evaluated by time-of-flight secondary ion mass spectrometry (TOF-SIMS), the distribution state of Li in the second crystal phase is approximately uniform. Effect of the Invention
[0010] The dielectric ceramic composition of the present disclosure has excellent stability in the high temperature range, and has excellent dielectric properties as well as durability. [Brief description of the drawings]
[0011] [Figure 1] 1 is a cross-sectional view that illustrates a capacitor according to a first embodiment. [Diagram 2] 2 is a flowchart showing a method for manufacturing a dielectric ceramic composition. [Diagram 3] 1 is an image showing the detection intensity of K+ in SA1 (Example). [Figure 4] 1 is an image showing the detection intensity of Ti+ in SA1 (Example). [Diagram 5] 1 is an image showing the detection intensity of Li + in SA1 (Example). [Figure 6] 1 is an image showing the detection intensity of K + in SA4 (comparative example). [Figure 7] 13 is an image showing the detection intensity of Ti+ in SA4 (Comparative Example). [Figure 8] 1 is an image showing the detection intensity of Li + in SA4 (comparative example). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] A preferred embodiment of the present disclosure is set forth below. An electronic component may include a dielectric material made of the above-mentioned dielectric ceramic composition, and an electrode provided on the dielectric material.
[0013] Hereinafter, embodiments embodying the present disclosure will be described in detail. In this specification, when a numerical range is described using "-", the range includes the lower limit and the upper limit unless otherwise specified. For example, the description "10-20" includes both the lower limit "10" and the upper limit "20". In other words, "10-20" has the same meaning as "10 or more and 20 or less".
[0014] 1. Dielectric ceramic composition The dielectric ceramic composition of the present embodiment is a dielectric ceramic composition including a first crystal phase made of an alkali niobate-based perovskite oxide and a second crystal phase having a non-perovskite structure. The second crystal phase contains Li and Ti, and when the second crystal phase is evaluated by time-of-flight secondary ion mass spectrometry (TOF-SIMS), the distribution state of Li in the second crystal phase is approximately uniform.
[0015] (1) First crystal phase The alkali niobate perovskite oxide forming the first crystal phase is preferably one represented by the following composition formula. <Formula of the first crystal phase> (K a Na b Li c C d ) e NbO f The alkali niobate perovskite oxide forming the first crystal phase contains at least the alkali metals K (potassium), Na (sodium), and Li (lithium), and the element C is at least one of the alkaline earth metals Ca (calcium), Sr (strontium), and Ba (barium), a, b, c, and d satisfy a+b+c+d=1, the coefficient e is 0.97≦e≦1.10, and the coefficient f is an arbitrary value.
[0016] In the above compositional formula, K (potassium), Na (sodium), Li (lithium), and element C (Ca, Sr, Ba) are arranged at the so-called A-site of the perovskite structure, and Nb is arranged at the so-called B-site of the perovskite structure. That is, the alkali niobate-based perovskite oxide is a perovskite oxide that contains at least one of alkali metals (K, Na, Li) and may contain alkaline earth metals (Ca, Sr, Ba) at its A-site, and contains Nb (niobium) at its B-site.
[0017] As the values of the coefficients a - f in the above compositional formula, among the combinations of values for which the perovskite structure is established, values preferable from the viewpoint of the dielectric properties (especially the relative permittivity) of the dielectric ceramic composition are selected. Specifically, the coefficients a - d satisfy 0 ≦ a ≦ 1, 0 ≦ b ≦ 1, 0 ≦ c ≦ 1, and 0 ≦ d ≦ 1 respectively, but a = b = c = 0 (that is, a composition that does not contain any of K (potassium), Na (sodium), and Li (lithium)) is excluded. The coefficients a and b of K (potassium) and Na (sodium) are typically 0 < a ≦ 0.6 and 0 < b ≦ 0.6. The coefficient c of Li (lithium) may be zero, but 0 < c ≦ 0.2 is preferable, and 0 < c ≦ 0.1 is more preferable. The coefficient d of element C (Ca, Sr, Ba) may be zero, but 0 < d ≦ 0.1 is preferable. The coefficient e with respect to the entire A-site is 0.97 ≦ e ≦ 1.10, but 1.00 ≦ e ≦ 1.08 is particularly preferable.
[0018] More specifically, the coefficient c will be described. c represents the amount of Li arranged at the A-site. Satisfying c ≦ 0.1 means that when the total amount of alkali metals and alkaline earth metals arranged at the A-site is 100 mol%, the amount of Li is 10 mol% or less. c is more preferably 0.010 ≦ c ≦ 0.100, more preferably 0.020 ≦ c ≦ 0.080, and even more preferably 0.030 ≦ c ≦ 0.060. If c is within the above range, the distribution state of Li in the second crystal phase described later can be preferably made substantially uniform. In the following description, c × 100 is also referred to as "the amount of Li (mol%) in the first crystal phase".
[0019] In the above composition formula, the valences of K, Na, and Li are +1, the valence of the element C (Ca, Sr, Ba) is +2, the valence of Nb is +5, and the valence of O (oxygen) is +2. The coefficient f takes any value such that the first crystal phase constitutes a perovskite oxide, and a typical value of the coefficient f is about 3. From the electrical neutralization condition of the composition, the coefficient af can be expressed by the following formula (1). (a+b+c+2·d)·e+5 ≒ 2·f ···(1)
[0020] The typical composition of the first crystal phase is (K,Na,Li,Ca,Ba) 1.07 NbO 3.07 (The coefficient ad is omitted.) This first crystal phase has K (potassium), Na (sodium) and Nb (niobium) as its main metal components, so the material is also called the "KNN material" and the first crystal phase is also called the "KNN phase." In addition, by selecting Ca (calcium) and Ba (barium) as the element C and further using Nb (niobium) as in this example, it is possible to obtain a dielectric ceramic composition that is inexpensive and has excellent properties.
[0021] The content of the first crystal phase is not particularly limited, but is preferably 90% by volume or more with respect to the entire dielectric ceramic composition. Hereinafter, the first crystal phase is also referred to as the "main phase".
[0022] (2)Second crystal phase The second crystal phase has a non-perovskite structure. Li and Ti are present in the second crystal phase. The Li of the second crystal phase may be, for example, Li derived from the raw material of the first crystal phase described below. The Ti of the second crystal phase may be, for example, Ti derived from the raw material of the second crystal phase.
[0023] The second crystal phase preferably contains, for example, one or more metal oxides selected from the following (a) and (b): (a)AB 2 O 4 Compounds based on cations (element A is a monovalent metal, element B is a divalent to hexavalent metal) (b)A 2 B6 O 13 Compounds based on cations (element A is a 1-2 valent metal, element B is a 2-5 valent metal) In the above composition formulas (a) and (b), the A site contains at least Li (lithium) and the B site contains at least Ti (titanium). The A site may contain an alkali metal or an alkaline earth metal, and the B site may contain a transition metal. Specifically, a compound can be used in which element A is one of the monovalent metals Li, Na, and K, which contains at least Li, and element B is one of the divalent to hexavalent metals Ti, Co, Fe, Mg, Ni, Zr, Mn, Al, Nb, Ta, and W, which contains at least Ti. For example, Li(Ti,Mn) 2 O 4 ,(Li,K) 2 (Ti,Nb) 6 O 13 It is possible to use Li(Ti,Mn) 2 O 4 In the composition formula, Ti and Mn are not 0 and are arbitrary blend ratios. (Li,K) 2 (Ti,Nb) 6 O 13 In the composition formula, Li and K are both non-zero and are any blend ratio, and Ti and Nb are both non-zero and are any blend ratio. The composition of the second crystal phase can be confirmed by TEM-EDS (energy dispersive X-ray spectroscopy).
[0024] The second crystal phase containing these compounds improves the sinterability by mixing with the first crystal phase, and also improves the insulating properties. It is also believed that it contributes to preventing abrupt fluctuations in capacitance between -55°C and 250°C. The content of the second crystal phase is preferably less than 10% by volume, more preferably 8% by volume or less, and further preferably 6% by volume or less, based on the entire dielectric ceramic composition. Hereinafter, the second crystal phase is also referred to as a "subphase." The content (volume %) of the second crystal phase can be determined, for example, by XRD (X-ray crystal structure analysis).
[0025] (3) Distribution of Li in the second crystal phase When the dielectric porcelain composition is evaluated for the second crystal phase by time-of-flight secondary ion mass spectrometry (TOF-SIMS), the distribution state of Li in the second crystal phase is substantially uniform. Hereinafter, the case where the first crystal phase contains K, that is, the case where 0 < a is satisfied in the composition formula will be described as an example.
[0026] The fact that the distribution state of Li in the second crystal phase is substantially uniform is defined as follows. For the dielectric porcelain composition, an observation cross section is obtained by the ion milling method. By TOF-SIMS, a 50 μm × 50 μm field of view in the observation cross section of the dielectric porcelain composition is evaluated as 512 pixels × 512 pixels. Pixels satisfying the following formula (I) are defined as specific pixels indicating the second crystal phase. A plurality of the above fields of view are observed, and a specific region in which at least 100 or more of the above specific pixels are continuous and the above specific region occupies 5% or more of the total area of the above field of view is selected as a specific field of view. I Li+ / (I K+ + 1) ≧ 0.1 ··· (I) (However, I Li+ is the detection intensity of Li + , and I K+ is the detection intensity of K + .) When the number of pixels satisfying the following formula (II) is less than 1000 in the above specific field of view, it is determined that the distribution state of Li in the second crystal phase is substantially uniform. I Li+ / (I Ti+ + 1) > 40 ··· (II), (However, I Li+ is the detection intensity of Li + , and I Ti+ is the detection intensity of Ti + .)
[0027] The number of pixels satisfying the above formula (II) is preferably 500 or less, more preferably 100 or less. The lower limit of the number of pixels satisfying the following formula (II) is 0. The number of pixels satisfying the above formula (II) can be controlled by adjusting the manufacturing method of the dielectric porcelain composition described later. For example, after calcining the raw material of the first crystal phase (main phase), LiNbO 3 is added and mixed, and by re-calcining, the number of pixels satisfying the above formula (II) can be reduced.
[0028] In addition, when the first crystal phase does not contain K (a = 0 in the composition formula) or is Na-rich (for example, 1.5×a < b in the composition formula), etc., K in the evaluation method + is replaced with Na + to evaluate the distribution state of Li in the second crystal phase.
[0029] Hereinafter, it will be specifically described with reference to experimental examples. FIGS. 6-8 are images showing the detection intensity of each ion by TOF-SIMS of SA4 (sample 4) which is a comparative example described later. FIG. 6 is an image showing the detection intensity of K + . FIG. 7 is an image showing the detection intensity of Ti + . FIG. 8 is an image showing the detection intensity of Li + . FIGS. 6-8 are all in the same field of view and are specific fields of view satisfying the above formula (I). In FIG. 6, the region observed as a portion with low detection intensity of K + (substantially black portion) corresponds to the second crystal phase. When FIG. 7 is superimposed on FIG. 6, it is confirmed that Ti exists in the second crystal phase. When FIG. 8 is superimposed on FIG. 6, it is confirmed that Li exists in the second crystal phase. In the specific field of view of FIGS. 6-8, the number of pixels satisfying the above formula (II) is 2005. That is, the number of pixels satisfying the above formula (II) is not less than 1000, and it is determined that Li is not distributed substantially uniformly in the second crystal phase. In FIG. 8, at the periphery of the second crystal phase, a portion where the detection intensity of Li + is higher than the surroundings is observed. That is, Li is unevenly distributed at the periphery of the second crystal phase.
[0030] On the other hand, FIG. 3-5 shows images of the detection intensity of each ion by TOF-SIMS of SA1 (sample 1) which is an example described later. + Figure 4 shows the detected intensity of Ti + Figure 5 shows the detection intensity of Li + The images in Figures 3 and 5 show the detection intensity of K. + The region observed as a region with low detection intensity (almost black region) corresponds to the second crystal phase. When FIG. 4 is superimposed on FIG. 3, it is confirmed that Ti is present in the second crystal phase. When FIG. 5 is superimposed on FIG. 3, it is confirmed that Li is present in the second crystal phase. In the specific visual field of FIG. 3-5, the number of pixels satisfying the above formula (II) is 0. That is, the number of pixels satisfying the above formula (II) is less than 1000, and it is determined that Li is distributed approximately uniformly in the second crystal phase. When FIG. 5 is observed, it is confirmed that in this embodiment, the entire second crystal phase is gray and Li is evenly present throughout the entire second crystal phase. In addition, it is confirmed that there is little gray shading and that Li is distributed approximately uniformly. Furthermore, in FIG. 5, at the periphery of the second crystal phase, Li + No area was observed where the detection intensity of Li was higher than the surrounding area. In other words, Li was not unevenly distributed around the periphery of the second crystal phase.
[0031] 2. Electronic Components The electronic component using the dielectric ceramic composition is not particularly limited. An example of the electronic component is a capacitor 1 as shown in FIG. 1. The capacitor 1 has a laminate 10 having a plurality of ceramic layers 13 (dielectric) (10 layers in this embodiment) formed of the dielectric ceramic composition, a first internal electrode 21 and a second internal electrode 22 alternately laminated via the ceramic layers 13, and a first external electrode 11 and a second external electrode 12 electrically connected to the first internal electrode 21 and the second internal electrode 22 and formed on the outer surface of the laminate 10. The capacitor 1 of this embodiment is a so-called chip capacitor in which the first internal electrode 21 and the first external electrode 11 are connected at the side surface and the second internal electrode 22 and the second external electrode 12 are connected at the opposing side surface.
[0032] According to the above-mentioned capacitor 1, since the ceramic layer 13 (dielectric) formed of a dielectric ceramic composition having excellent dielectric properties is used, it is possible to improve heat resistance, insulation, and temperature stability of capacitance. As a result, it is possible to improve reliability. As the internal electrode material, various metal materials such as Cu, Ag, Ni, etc. can be selected. In order to provide an inexpensive capacitor, it is preferable to use nickel (Ni) as the electrode material. Note that the configuration of the capacitor is not limited to the configuration of FIG. 1, and it is needless to say that it can be implemented in various configurations, such as other capacitors in which a dielectric is formed.
[0033] 3. Manufacturing method of dielectric ceramic composition 2 is a flow chart showing a method for producing a dielectric ceramic composition according to one embodiment. In this method, the first crystal phase (main phase) which is an alkali niobate perovskite oxide is calcined to LiNbO 3 The LiN phase is added, mixed and re-calcined to produce the dielectric ceramic composition. The second crystal phase (subphase) containing Ti is then mixed and calcined, and the mixture is degreased and fired to obtain the dielectric ceramic composition. Although the detailed mechanism is unclear, this manufacturing method can achieve a substantially uniform distribution of Li in the second crystal phase. The following description will be given with reference to FIG. 2.
[0034] In step T110, K is used as the raw material for the main phase (KNN phase). 2 CO 3 Powder, Sodium 2 CO 3 Powder, Li 2 CO 3 powder, CaCO 3 Powder, SrCO 3 Powder,BaCO 3 powder,Nb 2 O 5 Necessary raw materials such as powders are selected and weighed according to the coefficient in the composition formula of the main phase (for example, af in the composition formula of the main phase). Ethanol is then added to these raw material powders, and the mixture is wet-mixed in a ball mill for preferably 15 hours or more to obtain a slurry. In step T120, the mixed powder obtained by drying the slurry is calcined, for example, at 600° C. to 1100° C. in an air atmosphere for 1 hour to 10 hours to generate a first calcined powder of the main phase.
[0035] In step T122, LiNbO is added according to the value of a coefficient in the composition formula of the main phase (for example, af in the composition formula of the main phase). 3 The powder is weighed and added to the first calcined powder of the main phase. 2 CO 3 Powder and LiNbO added in step T122 3 The ratio (molar ratio) of the powders can be, for example, 0:100 to 80:20. In step T124, LiNbO 3 Ethanol is added to the calcined powder of the first main phase to which the powder has been added, and the mixture is wet-mixed in a ball mill for preferably 15 hours or more to obtain a slurry. The mixed powder obtained by drying the slurry is calcined for 1 hour to 10 hours at a specific temperature (e.g., 930°C) selected from a range of 600°C to 1100°C, for example, in an air atmosphere to produce a calcined powder of the second main phase.
[0036] In step T130, MnCO 3 Powder, TiO 2 powder, K 2 CO 3 Powder,BaCO 3 powder,Nb 2 O 5 Powder, ZrO 2 The necessary powders are selected from the powders and weighed according to the composition formula of the subphase. Ethanol is added to these raw powders and wet-mixed in a ball mill for preferably 15 hours or more to obtain a slurry. In step T140, the mixed powder obtained by drying the slurry is calcined, for example, at 600°C to 1100°C in an air atmosphere for 1 hour to 10 hours to generate a calcined powder of the subphase.
[0037] In step T150, the second main phase calcined powder and the subphase calcined powder are weighed, and a dispersant, a binder, and ethanol are added in a ball mill to pulverize and mix to form a slurry. The mixed powder obtained by drying the slurry is calcined, for example, in an air atmosphere at 600°C-1100°C for 1-10 hours to generate a calcined powder. In this embodiment, the preferred ratio of the subphase in the dielectric ceramic composition is specified in volume percent. Meanwhile, the mixing ratio of the second main phase calcined powder and the subphase calcined powder in step T150 is performed using the weights of the second main phase calcined powder and the subphase calcined powder. At this time, the relationship between the subphase ratio (weight percent) at the time of mixing in step T150 and the subphase ratio (volume percent) in the finally obtained lead-free piezoelectric ceramic composition can be empirically determined in advance.
[0038] In step T160, the calcined powder obtained in step T150 is again pulverized and mixed with a dispersant, a binder, and ethanol to form a slurry, which is dried and granulated by a spray dryer, and then uniaxially pressed at a pressure of, for example, 20 MPa to form a desired shape. Typical shapes of piezoelectric ceramics suitable for various devices as an embodiment of the present invention are disk-shaped, cylindrical, rectangular flat plate-shaped, etc. Then, a CIP process (cold isostatic pressing process) is performed at a pressure of, for example, 150 MPa to obtain a molded body. In step T170, the obtained molded body is held, for example, at 500°C-800°C in an air atmosphere for 2 hours to 10 hours to degrease the binder, and the degreased molded body is held, for example, at a specific temperature (for example, 1000°C) selected from 1000°C-1200°C in an air atmosphere for 2 hours to 50 hours to sinter, thereby obtaining a dielectric ceramic composition. The firing in step T170 is preferably a sealed firing performed in a state where the molded body is sealed in a sealed container. The reason for this is to prevent metal elements such as alkali metals (Li, Na, K) contained in the compact from disappearing to the outside during firing. As such a sealed container, for example, Alumina Saya A-1174 manufactured by Otake Ceram Co., Ltd. can be used. In step T180, the dielectric ceramic composition is processed according to the dimensional accuracy required for electronic parts. In step T190, the dielectric ceramic composition is evaluated.
[0039] When manufacturing the capacitor 1, steps 160, 170, and 180 may be performed as follows. The slurry obtained by grinding and mixing is then mixed with additive metals to produce a ceramic slurry, which is then formed into a sheet using a doctor blade method to obtain multiple ceramic green sheets of a specified shape and thickness. Next, a conductive paste mainly composed of nickel (Ni) is printed on a specified number of the ceramic green sheets. The printed conductive paste will become the internal electrode layer after firing. Next, multiple ceramic green sheets with the conductive paste printed on them are stacked together so that the conductive paste is exposed alternately from both sides. Finally, ceramic green sheets on which the conductive paste is not printed are stacked together to obtain an unfired laminate. This unfired laminate is heated at 250°C for 10 hours to remove the binder, and then heated in an atmosphere containing 0.1% oxygen and 0.1% hydrogen. -5 The laminate is then sintered at 1000°C-1200°C for 2-8 hours in a reducing atmosphere of humidified nitrogen-hydrogen mixed gas at 10 Pa. The end faces are polished by barrel polishing or sandblasting, and Ni paste is applied to both sides of the laminate. The laminate is then sintered in a reducing atmosphere (oxygen partial pressure of about 10 -5 The capacitor 1 is obtained by baking the laminated ...
[0040] The above-mentioned manufacturing method is one example, and various other steps and processing conditions can be used to manufacture the dielectric ceramic composition and electronic components.
[0041] 4. Effects of the Present Embodiment The dielectric ceramic composition of this embodiment has excellent heat resistance. For example, according to this embodiment, a dielectric ceramic composition having a Curie point Tc of 300° C. or higher can be obtained. Furthermore, the dielectric ceramic composition of this embodiment has good dielectric properties. For example, according to this embodiment, it is possible to obtain a dielectric ceramic composition having a relative dielectric constant of 1000 or more, a capacitance change rate within ±15% from −55° C. to 250° C. based on the capacitance at 25° C., and a dielectric loss tan δ of 0.02 or less. Furthermore, the dielectric ceramic composition of the present embodiment has high insulating properties and excellent durability.
[0042] Hereinafter, the reasons why the dielectric ceramic composition of the present embodiment has excellent heat resistance, good dielectric properties, high insulation properties, and excellent durability will be explained, but the present disclosure is not limited to these reasons. In this embodiment, it is presumed that Li and Ti are present at desired crystal sites, which contributes to the above-mentioned improvement in characteristics. Specifically, in this embodiment, Li is present almost uniformly in the second crystal phase. This is because the LiNbO 3 This is believed to be because the melting point of (1255°C) is higher than the firing temperature (e.g., 1000°C-1200°C), suppressing the diffusion of Li into the second crystal phase. It is also believed that some Li that diffuses into the second crystal phase reacts with the subphase raw material and exists approximately uniformly in the second crystal phase, improving the durability of the dielectric ceramic composition. Furthermore, by Li remaining on the first crystal phase side, Li is easily incorporated into the crystal structure of the first crystal phase. This is believed to lower the orthorhombic-tetragonal phase transition temperature in the first crystal phase. It is believed that Li exists in the desired crystal site in this way, and a dielectric ceramic composition that exhibits the above-mentioned effects was obtained. Moreover, according to this embodiment, it is presumed that the second crystal phase containing Ti fills the gaps between the particles of the first crystal phase, thereby making it dense (highly insulating).
[0043] 5. Use of dielectric ceramic compositions and electronic components The embodiments of the present disclosure are not limited to the dielectric ceramic composition, the electronic component (capacitor), and the manufacturing method of the dielectric ceramic composition, but may be applied to various other devices using the dielectric ceramic composition, methods for manufacturing such other devices, etc. Furthermore, the present invention is not limited to the above-mentioned embodiments, and may be embodied in various forms without departing from the spirit of the present invention. EXAMPLES
[0044] The present invention will be explained more specifically with reference to examples. In addition, samples SA1 to SA3 correspond to examples, and samples SA4 to SA6 correspond to comparative examples. In Tables 1 and 2, the comparative examples SA4 to SA6 are marked with "*".
[0045] 1. Preparation of Sample Composition For samples SA1-SA6, the dielectric ceramic compositions prepared according to steps T110-T190 of FIG. 2 were processed to a diameter of 13 mm and a thickness of 1 mm, and then Ag paste was baked at 800° C. on the entire upper and lower surfaces to form Ag electrodes. In steps T110 and T122, K is adjusted so that the value of the coefficient af in the composition formula of the first crystal phase is the amount ratio shown in Table 1. 2 CO 3 Powder, Sodium 2 CO 3 Powder, Li 2 CO 3 powder, Nb 2 O 5 Powder, CaCO 3 Powder, BaCO 3 Powder and LiNbO 3 The powder was weighed. The coefficient d represents the total amount of Ca and Ba. Samples SA1-SA6 have a first crystal phase ratio of 90 volume % or more. The ratio (mol%) of metal elements in the raw powder of the first crystal phase hardly changes even after sintering, so it is equivalent to the composition of the first crystal phase of each sample. In step T130, the types and amounts of the raw materials were appropriately selected so as to obtain a composition of the second crystal phase. In step T150, the second main phase calcined product and the subphase calcined product were weighed so as to obtain the subphase ratios shown in Table 1.
[0046] [Table 1]
[0047] 2. Evaluation of Sample Composition (1) Dielectric constant, dielectric loss, Curie point, resistivity For samples SA1-SA6, the dielectric constant (ε33T / ε0) and dielectric loss (tan δ) were measured using an LCR meter at 1KHz, 1Vrms, and 25°C. In addition, the capacitance was measured from -55°C to 350°C using an environmental tester and an LCR meter, and the point at which the capacitance was maximum was taken as the Curie point (Tc). Furthermore, the resistivity was measured by applying 100V for 60 seconds at a temperature of 25°C using a high resistivity meter HP4339B. The results are shown in Table 2.
[0048] (2)TOF-SIMS analysis For samples SA1 to SA6, the number of pixels satisfying the following formula (II), defined according to the description of the embodiment, was counted. The TOF-SIMS measurement conditions were as follows: Secondary ion polarity: positive Measurement area: 50μm x 50μm Number of pixels (per side): 512 pixels Static neutralization: yes Primary ion species: Bi 3 ++ Primary ion acceleration voltage: 30 kV Bunching: None (high spatial resolution measurement) Etching ions: O 2 + Etching ion acceleration voltage: 2 kV Etching rate: 20 nm / min (SiO 2 Conversion) After ion milling (CP processing) is completed, start TOF-SIMS measurement promptly (within 2 hours). In order to obtain a clean measurement surface, the measurement area in the TOF-SIMS device was 2 + By SiO 2 Measure after etching 40 nm equivalent. Integration conditions: K in the measurement range + The sum of the counts is 2.0 x 10 7 More than 2.5 x 10 7 Adjust it so that it becomes as follows.
[0049] Figures 3-5 are images showing the detection intensity of each ion by TOF-SIMS of SA1. Figures 6-8 are images showing the detection intensity of each ion by TOF-SIMS of SA4. The results are shown in Table 2 under the heading "I Li+ / (I Ti+ The number of pixels that satisfy the condition "+1)>40" is shown in the "Number of pixels that satisfy the condition "+1)>40" column. ILi+ / (ITi+ +1)>40 (II)
[0050] When the number of pixels satisfying the above formula (II) is less than 1000, it is determined that the distribution state of Li in the second crystal phase is substantially uniform. That is, SA1-SA3 are determined to have a substantially uniform distribution state of Li in the second crystal phase. SA4-SA6 are not determined to have a substantially uniform distribution state of Li in the second crystal phase.
[0051] [Table 2]
[0052] (3) Rate of change of capacitance The rate of change in capacitance from -55°C to temperatures near the Curie point (250°C-300°C) was determined for samples SA1-SA4. The rate of change in capacitance (%) was calculated by measuring the capacitance from -55°C to 350°C using an environmental tester and an LCR meter, and using the capacitance at 25°C as the standard. The results are shown in Table 3.
[0053] (4) Thermal cycle durability evaluation A thermal cycle test was conducted on samples SA1-SA4. The thermal cycle test, which changed the temperature between -40°C and +200°C, was conducted according to the following procedure. Note that the thermal cycle test, which changed the temperature between -40°C and +250°C, was conducted by substituting "+250°C" for "+200°C" in the following procedure. (i) Place each sample in a thermostatic chamber and evaluate the capacitance at room temperature (25°C) (initial value). (ii) Next, a thermal cycle in which the temperature is changed between -40°C and +200°C at a rate of 2°C / min is repeated 300 times (the holding time at -40°C, +200°C is 1 hour). (iii) Then, the capacitance is evaluated again at room temperature (25° C.) (capacitance after thermal cycling).
[0054] The change (%) in capacitance before and after the thermal cycle test was calculated using the following formula, and an evaluation was made as to whether the change was 10% or less. The results of the thermal cycle test in which the temperature was changed between -40°C and +200°C are shown in the "-40°C⇔200°C" column of Table 3. The results of the thermal cycle test in which the temperature was changed between -40°C and +250°C are shown in the "-40°C⇔250°C" column of Table 3. In Table 3, "≦10%" indicates that the change (%) in capacitance before and after the thermal cycle test was 10% or less. In Table 3, ">10%" indicates that the change (%) in capacitance before and after the thermal cycle test was greater than 10%. Capacitance change before and after thermal cycle test = ((Capacitance after thermal cycle - initial value) / initial value) x 100
[0055] [Table 3]
[0056] 3.Results As shown in Table 2, SA1-SA3 all had a Curie point of 300°C or higher, which was higher than that of SA4-SA6. In addition, SA1-SA3 all had a relative dielectric constant of 1000 or higher. SA1-SA3 all had a dielectric loss of 0.02 or less, which was lower than that of SA4-SA6. Furthermore, SA1-SA3 all had a higher resistivity than SA4-SA6.
[0057] As shown in Table 3, SA1 to SA3 all had excellent heat resistance, with the rate of change in capacitance being within ±15% from -55°C to 250°C. On the other hand, SA4, for example, had a rate of change in capacitance of 60.1% at 250°C, and thus did not have sufficient heat resistance. Additionally, SA1-SA3 all showed excellent durability, with capacitance fluctuations of less than 10% in a thermal cycle test in which the temperature was changed between -40°C and +200°C. Furthermore, of SA1-SA3, SA1 and SA2 all showed capacitance fluctuations of less than 10% in a thermal cycle test in which the temperature was changed between -40°C and +250°C, demonstrating even greater durability.
[0058] According to this embodiment, a dielectric ceramic composition having excellent stability in a high temperature range, excellent dielectric properties, and durability can be provided. Also, according to this embodiment, a dielectric ceramic composition having high insulating properties can be provided.
[0059] <Other embodiments (modifications)> The present invention is not limited to the above examples and embodiments, and can be embodied in various forms without departing from the spirit and scope of the present invention. [Explanation of symbols]
[0060] 1 ... Capacitor 10...Laminate 11...First external electrode (electrode) 12…Second external electrode (electrode) 13...Ceramic layer (dielectric) 21...First internal electrode (electrode) 22...Second internal electrode (electrode)
Claims
1. a first crystal phase made of an alkali niobate-based perovskite oxide; A dielectric ceramic composition comprising: The second crystal phase contains Li and Ti, A dielectric ceramic composition, wherein when the second crystal phase is evaluated by time-of-flight secondary ion mass spectrometry (TOF-SIMS), the distribution state of Li in the second crystal phase is approximately uniform.
2. A dielectric material comprising the dielectric ceramic composition according to claim 1; and an electrode provided on the dielectric.
Citation Information
Patent Citations
Dielectric ceramic composition, capacitor, and method for producing the dielectric ceramic composition
JP2013028484A
Dielectric ceramic composition and laminated ceramic capacitor
WO2006114914A1